The Changes of Amino Terminal Pro B-type Natriuretic Peptide (NT-proBNP) Concentration and Left Ventricular Ejection Fraction on Doxorubicin Chemotherapy Patients - Telly Kamelia (Jurnal Penyakit Dalam Indonesia, 2017)
Introduction. Cancer patients who received chemotherapy regimen containing doxorubicin has been known to have serious side effect in heart, called as cardiotoxicity. The measurement of NT-proBNP proposed to be used as a new parameter to identify and evaluate cardiotoxicity in cancer patients earlier before it has been manifested, superior than measurement of left ventricle ejection fraction (LVEF). The aims of this study to examine the changes of NT-proBNP concentration and LVEF on patients with cancer who receive chemotherapy regimen containing doxorubicin.